Thinking ecologically about clinical education in dentistry. (28th April 2020) - Perez, Arnaldo; Green, Jacqueline L.; Compton, Sharon M.; Patterson, Steven; Senior, Anthea
Abstract: Traditional approaches to clinical education (CE) in dentistry have primarily focused on the needs and interests of students (student‐centred), patients (patient‐centred) or individuals receiving care (person‐centred). Research has shown that giving priority to the interests of one stakeholder (eg students) may negatively affect the interests of others (eg patients, instructors and administrators). In this commentary, we discuss some limitations of traditional approaches to CE and suggest an eco‐centred approach that assumes that the interests of all stakeholders must be considered when planning CE due to the interdependent relationships between stakeholders. A description of this new approach is provided, whilst research and innovation are encouraged to develop an ecologically informed system of CE.